Resilience, Adaptive Peacebuilding and Transitional Justice How Societies Recover after Collective Violence - Natalya Clark, Janine; Ungar, Michael (Social Sciences, 2021)
This interdisciplinary volume, which includes eight case study chapters, offers a novel conceptual and empirical analysis of resilience, adaptive peacebuilding and transitional justice. It is the first volume of its kind to show how these three concepts can combine to inform individual and collective recovery from large-scale violence.